PLURALISME KOTA SOLO BERBASIS ISLAM RAHMATAN LIL ALAMIN - Mukhlis Fatkhurrohman (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
Religious pluralism is the historical basis for creating the spirit and dynamics in religions to be able to answer contemporary issues. Pluralism refers to the existence, togetherness and integrity of Pluralism that exists in Solo can be safe and peaceful because it holds Islamic teachings that promote Islam Rahmatan lil 'Alamin, Besides that, there are other tips in creating peace in the city of Solo, including: (1) There is a healthy awareness of Islam, (2) Dialogue between diverse people, (3) Exploring the spirit of pluralism in society, (4) Mutual care for places of worship, (5) Mutual exclusion in the form of inter-religious conflict, and (6) Mutual maintenance of inter-religious relations.